Supporting pupil premium attainment in science exams - Lean, J (2015)
The idea for the study originated from my own experience of having to enact interventions in School A to increase the level of exam attainment of Pupil Premium pupils in Science. I wanted to examine the impact that the interventions had over the course of a year to assess how they would translate into gains in exam scores. Three intervention types were trailed and evaluated by comparing the intervention group to a control group and the previous years results to see if there had been any effect. The intervention for the Summer School and Trips, Easter Revision and Breakfast Revision did not yield any statistical improvement for Pupil Premium students exam scores, but did produce a positive effect in attitude indicated in results from questionnaires. The intervention using a computer programmes called Tassomai yielded a positive result for Pupil Premium exam scores when compared to the control group and previous year’s results. The findings from this report will be used to inform further interventions in School in the following academic year.